Promoting linguistic complexity, greater message length and ease of engagement in email writing in people with aphasia: initial evidence from a study utilizing assistive writing software. Issue 1 (14th June 2016) - Thiel, Lindsey; Sage, Karen; Conroy, Paul
Abstract: Background: Improving email writing in people with aphasia could enhance their ability to communicate, promote interaction and reduce isolation. Spelling therapies have been effective in improving single‐word writing. However, there has been limited evidence on how to achieve changes to everyday writing tasks such as email writing in people with aphasia. One potential area that has been largely unexplored in the literature is the potential use of assistive writing technologies, despite some initial evidence that assistive writing software use can lead to qualitative and quantitative improvements to spontaneous writing. Aims: This within‐participants case series design study aimed to investigate the effects of using assistive writing software to improve email writing in participants with dysgraphia related to aphasia. Methods & Procedures: Eight participants worked through a hierarchy of writing tasks of increasing complexity within broad topic areas that incorporate the spheres of writing need of the participants: writing for domestic needs, writing for social needs and writing for business/administrative needs. Through completing these tasks, participants had the opportunity to use the various functions of the software, such as predictive writing, word banks and text to speech. Therapy also included training and practice in basic computer and email skills to encourage increased independence. Outcome measures included email skills, keyboard skills, email writing and written picture description tasks, and a perception of disability assessment. Outcomes & Results: Four of the eight participants showed statistically significant improvements to spelling accuracy within emails when using the software. At a group level there was a significant increase in word length with the software; while four participants showed noteworthy changes to the range of word classes used. Enhanced independence in email use and improvements in participants' perceptions of their writing skills were also noted. Conclusions & Implications: This study provided some initial evidence that assistive writing technologies can support people with aphasia in email writing across a range of important performance parameters. However, more research is needed to measure the effects of these technologies on the writing of people with aphasia, and to determine the optimal compensatory mechanisms for specific people given the linguistic–strategic resources they bring to the task of email writing.